Donde arde la memoria: La vuelta del poeta a la calle - Luengo, Ana (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2006)
This article studies the function of the poetry of memory of the Spanish Civil War in public spheres, seventy years after the war. Focusing in two poems, "El campo de batalla" by Angel González and "El pasado" by Luis García Montero, an analysis of the mechanisms of collective remembrance is carried out. Thus, the two poems are presented as a homage to the lyric written and published during the Republic and the War, and also as a meeting point for the memory of the defeated.